Résister - Crevier, Lyne (Ciel variable)

(untitled) (Les Productions Ciel variable, 2004)
Abstract In his series of self-portraits Version soft, the Moroccan artist Hicham Benohoud has metamorphosed his features by "martyrizing" his head in harsh photographs recalling those in Photomatons or mug shots. As his own model, he photographs himself as a common mannequin, which he subjects to metamorphoses that are sometimes farfetched, sometimes enigmatic, manifesting irony, violence, sadomasochism, or self-derision. As in his previous series, he questions identity through a multitude of modalities of the portrait that express, calmly and firmly, his lack of comfort with his situation, his culture, his country.